Motivasi Generasi Z dalam Mengunjungi Event Pewayangan: (Studi Kasus: Event Pekan Wayang Jawa Timur (PWJ)) - Calvin Briliant Arda Putra; Ayundik Permata Surya Ramadhani; Muhamad Alana Hafiz; Shadiq Hasan Al Rasyiq; Nova Rizmadhani Permata Putri; Santika Aurora Salsabill; Fasya Annisa (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
This study is motivated by several previous studies that conducted motivational research related to teenagers' visits to various types of events. The aim of this research is to validate the findings of previous studies by correlating external and internal motivations in the case study of the East Java Wayang Week (PWJ) event held at the “Taman Budaya Jawa Timur Cak Durasim” in Surabaya from November 6 to November 8, 2024. This study uses a mixed-method approach with an explanatory sequential design, where the researcher will analyze quantitative data regarding the general external motivations for attending the event. The findings from this quantitative analysis will then be further explored using a qualitative method to gain insights into the internal motivations of visitors to the event. Through the t-test results, a new finding was discovered, which differs from previous studies, where external motivation does not necessarily have a direct influence on the decision to attend the event. Interviews with several attendees of the East Java Wayang Week (PWJ) revealed that internal motivations also significantly influenced their decision to attend the event.